2018
DOI: 10.1053/j.gastro.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Utility of Total 68Ga-DOTATATE-Avid Tumor Volume in Patients With Neuroendocrine Tumors

Abstract: In a prospective study, we demonstrated the prognostic utility of Ga-DOTATATE TV in a large cohort of patients with NETs, in terms of PFS and disease-specific mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 43 publications
3
73
1
Order By: Relevance
“…Volumetric variables (WTV and TRE) determined by [ 68 Ga]Ga-DOTA-conjugated radiotracer PET/CT were assessed in a previous article, which revealed that the WTV determined by [ 68 Ga]Ga-DOTA-TATE PET/CT is associated with prognosis [33]. However, a limitation of this study was the heterogeneous patient population in terms of treatment, including surgery, PRRT, liver- directed therapy, and systemic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Volumetric variables (WTV and TRE) determined by [ 68 Ga]Ga-DOTA-conjugated radiotracer PET/CT were assessed in a previous article, which revealed that the WTV determined by [ 68 Ga]Ga-DOTA-TATE PET/CT is associated with prognosis [33]. However, a limitation of this study was the heterogeneous patient population in terms of treatment, including surgery, PRRT, liver- directed therapy, and systemic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Bone FD has been visualized with conventional SSTRs scintigraphy using 111 ln-pentetreotide, suggesting cell surface over-expression of SSTRs by fibrous dysplastic cells (119). The introduction of 68 Ga-DOTA-conjugated-peptides into clinical practice has enabled the employment of PET-imaging in targeting lesions, characterized by SSTRs-overexpressi on (18,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Papadakis et al reported intensely increased 68 Ga-DOTATE (radiolabeled somatostatin analogue suitable for PET-imaging, which targets SSTRs) activity on PET/CT, by a biopsy proven FD lesion in the temporal bone (22).…”
Section: Fibrous Dysplasiamentioning
confidence: 99%
“…68 Ga-DOTA-compounds are somatostatin (SST) analogs, radiolabeled with the positron emitting isotope gallium-68 ( 68 Ga) through the chelator 1,4,7,10-tetraazacyclododecane-1, 4,7,10-tetraacetic acid (DOTA) (18). The employment of these compounds enables highly efficient targeting of lesions which are characterized by cell-surface over-expression of SST receptors (SSTRs), such as neuroendocrine tumors (NETs), for which PET/CT imaging with 68 Ga-DOTA-compounds is evolving as the imaging standard of reference (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…Scarce pertinent literature reports a significant correlation between whole-body SRETV (SRETVwb) and disease progression after PRRT. Tirosh et al [97] reported that " 68 Ga-DOTATATE TV" (equalling SRETVwb) > 7.0 mL was significantly correlated with a higher risk for disease progression, while " 68 Ga-DOTATATE TV" > 35.8 ml was associated with higher diseasespecific mortality. Toriihara et al [98] reported an association between " 68 Ga DOTATATE ∑SRETV"…”
Section: Functional Imagingmentioning
confidence: 99%